Classification of Standing Types at PT. Work Locations. Sustainable Forest Tusam in Krakap Dusun, Umang Village, Linge District, Central Aceh District - Jamilah, Maryam; Afrida, Nur (MultiTech Publisher, 2024)
PT. Tusam Hutani Lestari is a company with an area of ± 97,300 Ha which has an Industrial Plantation Forest Concession Rights permit number 452/Kpts-11/92 dated 14 May in Aceh Province which is in the districts of Central Aceh, North Aceh, Bener Meriah and Bireuen. With a large working area, the forest area is divided into 6 working blocks, namely the Mount Salak block, Blangkuyu block, Lampahan block, Burni Telong block, Bidin block and Jambu Aye block, making this area have varied biodiversity. This observation aims to determine the diversity of types of stand distribution found on mixed forest land and to determine the value of the important value index (INP) for a type of stand at the PT work site. Tusam Sustainable Forest. The results show that there are 8 types of stands or trees with a total of 17 individuals in the mixed forest area. The dominant important value index (INP) is found in Eucalyptus trees at 60.57% and Pine at 58.66%, while the INP for all plant types in mixed forest area cover is 300% and is included in the high value, and the diversity index for the growth rate of mixed forest land cover shows that the PT Tusam Hutani Lestari work area is included in the medium criteria.